2017
DOI: 10.1159/000477332
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations and Prognostic Factors of <b><i>Pneumocystis jirovecii</i></b> Pneumonia without HIV

Abstract: Introduction:Pneumocystis jirovecii pneumonia (PCP) can occur in HIV patients but also in those without HIV (non-HIV PCP) but with other causes of immunodeficiency including malignancy or rheumatic diseases. Objective and Methods: To evaluate the clinical presentation and prognostic factors of non-HIV PCP, we retrospectively reviewed all patients diagnosed as having PCP without HIV at Kameda Medical Center, Chiba, Japan, from January 2005 until June 2012. For the purpose of examining a prognostic factor for no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…However, several studies still report high mortality rates among HIV-uninfected patients probably due to the greater intensity of the inflammatory response, the acuteness of symptoms, the more frequent progression to respiratory failure requiring tracheal intubation [8], and also the influence of different management practices [9][10][11][12][13].…”
mentioning
confidence: 99%
“…However, several studies still report high mortality rates among HIV-uninfected patients probably due to the greater intensity of the inflammatory response, the acuteness of symptoms, the more frequent progression to respiratory failure requiring tracheal intubation [8], and also the influence of different management practices [9][10][11][12][13].…”
mentioning
confidence: 99%
“…In HIV-positive patients, highly active antiretroviral therapy (HAART) and antimicrobial prophylaxis in high-risk patients have substantially lowered the incidence and mortality of PJP. PJP also occurs in HIV-uninfected immunocompromised patients, and in this population, PJP mortality has been increasing [ 1 , 2 ]. Mortality attributable to PJP in patients with HIV ranges between 10% and 20%, while mortality in HIV-negative patients ranges between 30% and 50% [ 3–5 ].…”
mentioning
confidence: 99%
“…In other studies, it was reported that low serum albumin levels and mechanical ventilation were independent predictors of mortality by multivariate analyses (40,41). In our study, performance status of 2-4, treatment delay and high (severe) disease activity were unfavorable prognostic factors by an univariate analysis (42). More studies and analyses are needed.…”
Section: Prognosismentioning
confidence: 47%